Scratch. Didactic strategy to learn the multiplication table in new school - Vivas Silva, Carlos Julio; Murillo Chiquillo, Zulma Lucía; Cristancho Chinome, Jaime Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
When making an analysis of the Institutional Educational Project, the results of the SABER tests on Mathematics, Curriculum, Synthetic Index of Educational Quality, New School Model, methodology and appropriation of the educational system in the Institution, we see the need to strengthen multiplicative processes and favouring numerical thinking in the integral education of the student; reinforce learning in the resolution of basic operations and help develop skills that respond efficiently to solve mathematical problems of daily life. The objective was to implement a didactic strategy to facilitate the learning of the multiplication tables with the use of Scratch methodology. The methodology has a qualitative approach, type of educational action research. For this, a diagnosis was made, identifying weaknesses and strengths of the students. micro-curricular and didactic activities were designed to strengthen the learning corners, giving the student the opportunity to enjoy class environments, think, feel and do; being an active subject, giving initiatives in their self-learning, stimulating the understanding of procedures, generating spaces for calculation and discovery. As results, it was evidenced with the use of software that the students achieved advances in the learning process by improving the reasoning capacity of the multiplication tables.